Development and validation of scale using Rasch analysis to measure students' entrepreneurship readiness to learn embedded system design course - Intisar Ibrahim, Ridwan; Kamilah Radin, Salim; Zulkifli, Adam,; Izzeldin Ibrahim, Mohamed Abdelaziz; Elfadil, Nazar A. (Elsevier B.V., 2020)
Embedded systems are growing rapidly as the technology paves the way for the rise of future of smart manufacturing through a wide range of industries. The intensity demands of innovation required a steady supply of innovative and entrepreneurship engineers to ensures the industry players have a sustainable supply of talent to fuel their growth and investments. The university acknowledge the current and future demand of the labour market by offering embedded system course that are developed to equipped the next generation engineers with innovation and entrepreneurship skills to enable them to turn their ideas into reality. This paper developed and validated a scale to measure the student entrepreneurship skills readiness for embedded systems design course using the Rasch analysis.The content validity results show that CVR is 0.92 and CVI is 0.96 indicating an excellent content validity. The pilot test result show that the scale Cronbach alpha is 0.80 indicating excellent scale reliability. The construct validity of the scale was evaluated using WINSTEPS version 3.92.1, with results indicated that all the items of the scale fit the Rasch model with satisfactoryfit index and showedexcellent consistency, with reliability alpha of 0.99 foe items and 0.75 for persons. The findings depicted that most of the students have poor business and entrepreneurship skills, such as marketing and negotiation abilities. Therefore, higher learning institutions need to embed acquirable entrepreneurial skills in the prerequisites courses to provide adequate training to the students, increasing their creativity and maximizing their potential to be successful entrepreneurs.